Menjelang Masuknya Islam Di Ujung Timur Pulau Jawa - nfn. Masyhudi (Berkala Arkeologi, 2007)
Very little archaeological data regarding the development of Islam in the Banyuwangi area is currently available. From this minimal archaeological data, it shows that there is no time conformity with the historical chronology of the development of Islam in the Banyuwangi Regency area. Related to this, academic research or studies in the field of archeology are still needed to support or find the truth of the history of the development of Islam in the Banyuwangi area, and in general for the purpose of forming and strengthening national identity.